Implementation of the Continuing Professional Development Program (PKB) for Subject Teachers - Hani Qurrotul Aini; Farid Adriansyah; Febri Rahmawati; Shauwmi Nur Azizah; Wiji Hidayati (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
Continuing Professional Development (CPD) is a program designed to enhance teachers’ competencies and professionalism on an ongoing basis. This study aims to analyze the implementation of CPD for subject teachers at MTs Negeri 9 Bantul, identify its impact on teacher professionalism, and examine the challenges and development strategies associated with the program. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with the principal of MTs Negeri 9 Bantul and document analysis. The data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that CPD is implemented through Subject Teacher Consultation Forums (Musyawarah Guru Mata Pelajaran / MGMP), In-House Training (IHT), workshops, and online training provided through the Ministry of Religious Affairs’ PINTAR platform. Based on interview and documentation data, these activities encourage teachers to engage more actively in professional collaboration, utilize digital learning media such as Quizizz, Wordwall, and Canva for Education, and implement innovative learning models such as Project-Based Learning and blended learning. The findings also indicate that CPD contributes to the improvement of teachers’ pedagogical and digital competencies, which in turn enhances students’ participation and learning motivation. Program evaluation is conducted through regular coordination meetings and digital monitoring via the Si Panjat Padi system. However, several challenges remain, including limited time, insufficient funding, and low teacher participation in scientific publication activities. To address these challenges, the madrasah develops CPD programs based on the results of academic supervision and National Assessment (ANBK) data. This study demonstrates that CPD plays an important role in supporting teacher professionalism and improving the quality of learning in madrasahs.